2012
DOI: 10.1111/j.1365-2109.2012.03172.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonia on the electrolyte status of an Indian major carp Catla catla

Abstract: Ammonia is present in the aquatic environment due to agricultural runoff, sewage effluents and decomposition of biological waste. High level of ammonium in the aquatic environment or in aquaculture farms is a serious problem for aquatic organisms. In the present investigation, the sublethal effects of total ammonia nitrogen (TAN) at 9.98 mg L À1 on plasma electrolytes (Na + , K + and Cl À ) level of Indian major carp Catla catla fingerlings was studied for a period of 35 days under semistatic conditions. Expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
1
5
0
1
Order By: Relevance
“…The visualized anomalies in the tissues of fingerlings exposed to ciprofloxacin are associated with the lowering of plasma inorganic ions. Dinesh et al reported that prolonged exposure of fish exposed to xenobiotics might leads to impairment of ion oregulation, which in turn affects the physiology and metabolic activities of the fish 90 . Multiple functional activities of gills are closely associated with the epithelial chloride cells, which consists of a specialized membrane‐bound enzyme (Na + /K + ‐ATPase) for ion homeostasis 91,92 .…”
Section: Discussionmentioning
confidence: 99%
“…The visualized anomalies in the tissues of fingerlings exposed to ciprofloxacin are associated with the lowering of plasma inorganic ions. Dinesh et al reported that prolonged exposure of fish exposed to xenobiotics might leads to impairment of ion oregulation, which in turn affects the physiology and metabolic activities of the fish 90 . Multiple functional activities of gills are closely associated with the epithelial chloride cells, which consists of a specialized membrane‐bound enzyme (Na + /K + ‐ATPase) for ion homeostasis 91,92 .…”
Section: Discussionmentioning
confidence: 99%
“…High levels of blood creatinine are found in renal dysfunction or muscle injury [35]. Levels of specific ions such as sodium (Na+), potassium (K+), chloride (Cl−) and bicarbonate (HCO3−) are used as biomarkers of electrolyte imbalance [36]. Electrolytes promote fluid balance via maintenance of blood volume, fluid absorption and generation of impulses.…”
Section: Introductionmentioning
confidence: 99%
“…Por estarem relacionados à fração proteica da dieta e seu processo cataólico, esses elementos geram resíduos nitrogenados que são eliminados nas fezes ou em forma de amônia pelas brânquias (Boyd, 1992). O acúmulo de amônia na água pode resultar em aumento nas concentrações desse parâmetro no sangue e tecidos de peixes, o que pode ocasionar a redução do desempenho zootécnico dos animais, e concentrações mais elevadas podem provocar toxicidades subletal e letal (Dinesh, 2013).…”
Section: Introductionunclassified